Human tooth bank: sociocultural profile of a group of donors - Mariane Moreira Poletto; Mônica Moreira; Marília Moreira Dias; Maria da Graça Kfouri Lopes; Osmir José Lavoranti; Eduardo Pizzatto (Faculdade São Leopoldo Mandic, 2010)
Objective: To survey the sociocultural profile of a specific group of individuals who donated teeth to the Human Tooth Bank of Positivo University, Curitiba, Paraná, Brazil. Methods: The research consisted of a questionnaire containing the following information about: Patient's age, sex, occupation, education, reason for tooth loss and intention to replace the missing tooth by means of prosthesis or implant. The questionnaire was filled out by 50 patients after having the extraction procedure performed and donating the dental organ. The data were compiled and analyzed by means of descriptive and multivariate statistics. Results: The sociocultural profile of the donor was basically composed of individuals in the age group between 30 and 50 years, with educational level ranging from zero to nine or more years of formal schooling. Caries disease was the most frequent reason for tooth loss (36%), followed by periodontal disease (34%). Of the donors analyzed, more than half did not intend to replace the tooth. Furthermore, according to the multivariate analysis, the most relevant factors for assessing the profile of donors were the variables age, orthodontic indication, caries and periodontal disease. Conclusion: This information was shown to be relevant for structuring the oral health care services, as well as in the strategy for obtaining teeth from the Public Health Units.